Рестрикционное картирование внехромосомного элемента рСА25 Erwinia carotovora - Сергеева, Ж.Ю.; Товкач, Ф.И. (Видавничий дім "Академперіодика" НАН України, 2009)
Проведено фiзичне картування позахромосомного елемента рСА25 Erwinia carotovora i його транспозонного варiанта рСА25::Tn9. Плазмiда рСА25 належить до найбiльш поширеного серед ервiнiй розмiрного класу позахромосомних ДНК завдовжки 9,8 т. п. н. На основi отриманих даних побудовано попередню рестрикцiйну карту плазмiди i виявлено мiсце вбудовування транспозону Tn9 у плазмiдну ДНК. The restriction site mapping of Erwinia carotovora’s extrachromosomal element pCA25 and its transposon variant рСА25::Tn9 has been performed. Plasmid pCA25 belongs to the most widespread size class of erwinia’s extrachromosomal DNAs 9.8 kb. The preliminary restriction map of the plasmid has been created, and the site of the Tn9 transposon incorporation has been detected corresponding to the obtained data.